1) 5x^2 - 15x - x - 3 =0
Объяснение:
1) D= b^2-4ac= 196+60= 256 = 16^2
x1= -14+16/10= 1/5
x2= - 14-16/10= - 3
2) D=25-16=9=3^2
x1= 5+3/2=8/2=4
x2= 5-3/2=2/2=1
3) 10x^2 + 5x-3/5=0
50x^2 +25x-3=0
D= 625+600=1225=35^2
x1= -25+35/100= 1/10
x2= - 25-35/100= - 3/5
4) x^2 +6x-5x=0
x^2+x=0
D= 1=1^2
x1= - 1+1/2=0
x2= - 1-1/2=-1
5) 2-3x-5x^2=0
-5x^2-3x+2=0
5x^2+3x-2=0
D=40+9=49=7^2
x1=-3+7/10= 2/5
x2=-3-7/10= - 1
6) x^2-4x+4=3x-8
x^2-4x+4-3x+8=0
x^2-7x+12=0
D=49-48=1=1^2
x1=7+1/2= 4
x2=7-1/2= 3
7) 5(x^2+4x+4)= -50
5x^2+20x+20= -50
5x^2+20x+20-50=0
5x^2+20x+70=0
x^2+4x+14=0
D= 16-56=-40 - корней нет
ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите